MENTORING PRACTICES IN PNU PARTNER SCHOOLS : TOWARDS POLICY CREATION IN CAPACITY BUILDING OF COOPERATING TEACHERS FOR EFFECTIVE MENTORING - Josephine M Calamlam; Darryl Roy T; Annabelle DC Palmeiry; Ma. Victoria J Delos Santos (Program Pascasarjana Universitas Negeri Jakarta, 2016)
The practice of mentoring student teachers seeks the much needed intervention and reform in the preparation of future teacher professionals who will eventually implement the K-12 Curriculum in the Philippines. The present study investigated on the perception of student teachers on the way they were mentored during their practice teaching in the selected partner schools. Additionally, this paper presents the beliefs and practices of cooperating teachers which student teachers perceive to be effective in the mentoring process. Data gathered from surveys and interviews with student teachers and cooperating teachers for this study pointed the strengths of the mentoring program as well as pitfalls that need to be addressed. The cooperating teachers in the different partner schools identified elements which are believed to be areas of concern that make them feel the need to undergo capability building. The findings presented here are intended to inform the development of policies in building cooperating teachers‟ capability for effective mentoring.